2018
DOI: 10.1017/s0016756818000134
|View full text |Cite
|
Sign up to set email alerts
|

Geochronological and geochemical studies of the OIB-type Baiyanghe dolerites: implications for the existence of a mantle plume in northern West Junggar (NW China)

Abstract: In this paper, zircon U–Pb geochronology, major and trace elements, and Sr–Nd isotope geochemistry of the Baiyanghe dolerites in northern West Junggar of NW China are presented. The U–Pb dating of zircons from the dolerites yielded ages of 272.2±4 Ma and 276.7±6.2 Ma, which indicate the emplacement times. The dolerites are characterized by minor variations in SiO2(46.89 to 49.07 wt%), high contents of Al2O3(13.60 to 13.92 wt%) and total Fe2O3(11.14 to 11.70 wt%), and low contents of MgO (2.67 to 3.64 wt%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 166 publications
(273 reference statements)
0
12
0
Order By: Relevance
“…The West Junggar region then experienced a postorogenic stage (Choulet et al, 2012(Choulet et al, , 2011; Fig. 10) associated with intraplate magmatism and marked by multiple events of dyke intrusions until the late Triassic (Miao et al, 2019;. In the Baiyanghe area, the late Devonian felsic volcanic and pyroclastic rocks of the Tarbagatay Group, and the late Carboniferous Yangzhuang granite porphyry represent the U source rocks for the mineralisation in the Baiyanghe deposit proposed in previous studies (Li et al, 2015;Mao et al, 2014;Shabaga et al, 2013;Zhang et al, 2019Zhang et al, , 2020.…”
Section: The Source(s) Of Uraniummentioning
confidence: 70%
See 2 more Smart Citations
“…The West Junggar region then experienced a postorogenic stage (Choulet et al, 2012(Choulet et al, , 2011; Fig. 10) associated with intraplate magmatism and marked by multiple events of dyke intrusions until the late Triassic (Miao et al, 2019;. In the Baiyanghe area, the late Devonian felsic volcanic and pyroclastic rocks of the Tarbagatay Group, and the late Carboniferous Yangzhuang granite porphyry represent the U source rocks for the mineralisation in the Baiyanghe deposit proposed in previous studies (Li et al, 2015;Mao et al, 2014;Shabaga et al, 2013;Zhang et al, 2019Zhang et al, , 2020.…”
Section: The Source(s) Of Uraniummentioning
confidence: 70%
“…Lithofacies paleogeographical studies and paleomagnetic research revealed that a remnant oceanic basin still existed in the northern West Junggar region until 300 Ma ago (Choulet et al, 2011;Wang, 2006;Wang et al, 2007), which strongly argues in favour of an ocean ridge subduction model to interpret the extensive late Carboniferous magmatism in West Junggar (Geng et al, 2011(Geng et al, , 2009Tang et al, 2010aTang et al, , 2010bTang et al, , 2009Yang et al, 2012;Yin et al, 2011Yin et al, , 2010. The northern West Junggar region then entered in a post-orogenic stage (Choulet et al, 2012(Choulet et al, , 2011 associated with intraplate magmatism characterised by multiple events of dyke intrusions during the early Permian-middle Triassic (Miao et al, 2019;Yi et al, 2014), including diorite porphyry (290±18 Ma, 222±18 Ma), dolerite (277±6 Ma, 272±4 Ma), diabase (255 Ma), and alaskite (255±2 Ma, 246±1 Ma).…”
Section: Regional Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…2a). They were emplaced during the Early Permian to Late Triassic (Ma et al 2010;Miao et al 2019). Miao et al (2019) suggested that the diabase dykes in the Baiyanghe deposit were probably derived from an ocean-island basalts (OIB)-like mantle source and associated with a mantle plume tectonic setting.…”
Section: Geology Of the Baiyanghe Depositmentioning
confidence: 99%
“…The geochronological framework that includes the magmatism and U-Be mineralization in the Baiyanghe deposit. The data are from:Ma et al 2010, Zhang and Zhang 2014, Yi 2016Miao et al 2019, Xia 2019 …”
mentioning
confidence: 99%